PENGABDIAN PENINGKATAN KETERAMPILAN MENYUSUN PROPOSAL KEGIATAN DAN KEUANGAN ORGANISASI PEMUDA DI ACEH TIMUR - Jamali Jamali; Muhammad Jamil; Teuku Muana Refi; Erni Wiriani; Abdul Aziz (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2021)
The purpose of this community service is; 1) Disseminate the existence of youth organizations' roles in development, 2) Provide awareness for citizens to be able to participate in activities/become active members and administrators. 3) Provide skills training for administrators/members to determine feasible work programs to be implemented, and 4) Provide skills in making proposals and financial reports within the organization. The stages of implementing the activities consist of; 1) Lectures and questions and answers, 2) Provide technical training, and 3) Assistance in making activity proposals. The results of service activities include; 1) The PPM activity has succeeded in socializing the existence of the role of youth organizations in development, 2) The activity has succeeded in providing citizens' awareness to be able to participate in activities/become active members and administrators. 3) The training activities have succeeded in encouraging youth or organizational members to determine possible work programs to be implemented, 4) The training activities have provided skills to make proposals and financial reports in youth organizations, and 5) Established partnerships and cooperation between the youth of East Aceh Regency, PKBM Smart Mandiri Peureulak and Akademi Keuangan Perbankan Nusantara.